2014
DOI: 10.7763/ijesd.2014.v5.510
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Promoter Identification of Acetoacetyl-CoA Thiolase Gene from Oil Palm, Elaeis guineensis Jacq.

Abstract: Abstract-Acetoacetyl-CoA thiolase (AACT, β-ketothiolase) is an enzyme that catalyzes the biological Claisen condensation of two molecules of acetyl-CoA to form acetoacetyl-CoA. In plants, AACT is known to be involved in the early step of mevalonate pathway which is essential in producing isoprenoid compounds such as sterols, carotenoids and growth regulators. In order to study this gene, we attempt to clone the gene from oil palm. The AACT gene was cloned from a genomic library of oil palm using a homologous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…At the initial step of the MVA pathway, AACT catalyzes the biological Claisen condensation of two molecules of acetyl-CoA to form acetoacetyl-CoA, which is essential in producing terpenoid and isoprenoid compounds such as sterols, carotenoids and growth regulators. At present, the study of AACT genes in plants is less, what we do know is that AACT is found in Elaeis guineensis Jacq, Ganoderma lucidum and Bacopa monnieri (Rahman and Samian et al, 2014;Fang et al, 2013;Vishwakarma et al, 2012). However, the AACT gene has not been reported in C. nobile so far.…”
Section: Introductionmentioning
confidence: 83%
“…At the initial step of the MVA pathway, AACT catalyzes the biological Claisen condensation of two molecules of acetyl-CoA to form acetoacetyl-CoA, which is essential in producing terpenoid and isoprenoid compounds such as sterols, carotenoids and growth regulators. At present, the study of AACT genes in plants is less, what we do know is that AACT is found in Elaeis guineensis Jacq, Ganoderma lucidum and Bacopa monnieri (Rahman and Samian et al, 2014;Fang et al, 2013;Vishwakarma et al, 2012). However, the AACT gene has not been reported in C. nobile so far.…”
Section: Introductionmentioning
confidence: 83%